Implementasi Long Short-Term Memory pada Chatbot Informasi Akademik Teknik Informatika Unila - Puput Budi Wintoro; Hilmi Hermawan; Mona Arif Muda; Yessi Mulyani (Universitas Bandar Lampung (UBL), 2022)
The times have made technology develop rapidly and rapidly, one of which is artificial intelligence. According to an Accenture survey, s can help organizations with up to 30% operational costs and users enjoy having 24/7 instant access to the answers they order. However, there are many organizations and companies that have not used s to facilitate business, one of which is the Informatics Engineering Study Program, University of Lampung (PSTI Unila). The purpose of this research is to able to apply the Long Short-Term Memory (LSTM) algorithm to the academic information at PSTI Unila and demonstrate the accuracy of the algorithm. Broadly speaking, this research consists of 4 stages: data collection and exploration, data preparation, building model and training, and testing the model. The model is tested using the user validation method which gets an accuracy of 99%. With these accurate results, this model is quite feasible to be used as a place for students to ask questions about PSTI Unila academic information.